2020
DOI: 10.3390/ani10030441
|View full text |Cite
|
Sign up to set email alerts
|

Association Analysis to Copy Number Variation (CNV) of Opn4 Gene with Growth Traits of Goats

Abstract: Extensive research has been carried out regarding the correlation between the growth traits of livestock and genetic polymorphisms, including single nucleotide polymorphisms and copy number variations (CNV). The purpose of this study was to analyze the CNV and its genetic effects of the Opn4 gene in 284 Guizhou goats (Guizhou black goat: n = 186, Guizhou white goat: n = 98). We used qPCR to detect the CNV of the Opn4 gene in Guizhou goats, and the classification results were correlated with the corresponding i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Association analysis has been widely used for analyzing the effect of gene polym phism on quantitative traits in animals [34][35][36]. Target sequence and reference sequ primers were used to amplify each sample by qPCR (each group has three replicatio Then, we analyzed the qPCR results by referring to previous studies in our labora [37].…”
Section: Discussionmentioning
confidence: 99%
“…Association analysis has been widely used for analyzing the effect of gene polym phism on quantitative traits in animals [34][35][36]. Target sequence and reference sequ primers were used to amplify each sample by qPCR (each group has three replicatio Then, we analyzed the qPCR results by referring to previous studies in our labora [37].…”
Section: Discussionmentioning
confidence: 99%
“…The quantitative PCR primer pairs (CNV1, CNV2 and CNV3) were used to detect the copy number variations of the PPP3CA gene in different individuals, and they were designed using Primer Blast ( accessed on 12 September 2021). Following a previous study, the MC1R gene was used as internal control [ 20 ]. Additionally, all primers’ pair sequence information is shown in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the qPCR results of the copy number of the PPP3CA gene were analyzed using the 2*2 − ∆CT method, where ∆CT = Ct target − Ct internal , Ct target is the number of cycles when the target gene amplification reaches the threshold and Ct internal is the cycle number when the internal reference gene amplification reaches the threshold. The CNVs were divided into three types, Gain (2 × 2 − ∆CT ≥ 3), Loss (2 × 2 − ∆CT < 2), and Medium (2 × 2 − ∆CT = 2) [ 20 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CNVs can directly modulate phenotype by changing gene copy number (CN) and gene structure or disturbing gene regulatory sequence. Previous studies have shown that SH3RF2 -CNV was significantly associated with growth and carcase traits in chickens (Jing et al ., 2020), Opn4 -CNV were significantly associated with body weight traits (Li et al ., 2020). Numerous studies have reported the association between gene-CNV and growth traits (Feng et al ., 2020; Shi et al ., 2020; Zhang et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%